2009
DOI: 10.1111/j.1524-4725.2008.34379.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma Skin Cancers of the Ear: Correlation Between Subanatomic Location and Post-Mohs Micrographic Surgery Defect Size

Abstract: MMS defects of the ear are larger in nonvisible parts of the ear. As a group, MMS defects on the ear were larger than those on the nose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
(31 reference statements)
0
11
0
1
Order By: Relevance
“…The following additional search limitations were placed on the evidence review: In total, 161 primary articles were identified and analyzed for the development of the supporting evidence tables for the MMS AUC: 53 for basal cell carcinoma (BCC), 6-58 63 for squamous cell carcinoma (SCC), 6,[8][9][10]13,15,16,[18][19][20][21]23,24,29,36,[39][40][41][42]45,46,48,49,54, 23 for LM and melanoma in situ, 10 10,103,[182][183][184][185][186] In the majority of publications, more than 1 neoplasm was reported per study.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…The following additional search limitations were placed on the evidence review: In total, 161 primary articles were identified and analyzed for the development of the supporting evidence tables for the MMS AUC: 53 for basal cell carcinoma (BCC), 6-58 63 for squamous cell carcinoma (SCC), 6,[8][9][10]13,15,16,[18][19][20][21]23,24,29,36,[39][40][41][42]45,46,48,49,54, 23 for LM and melanoma in situ, 10 10,103,[182][183][184][185][186] In the majority of publications, more than 1 neoplasm was reported per study.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…High-risk areas on the face, which include the ear, can cause significant morbidity and have higher risks of metastasis and recurrence, even after Mohs surgery. 3,4 In this study, we compared the incidence of NMSC on the ear with that on the head and the rest of the body. Our findings add to the existing reports of NMSC on the ear.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although NMSC has a low mortality rate, its treatment can cause morbidity and results in a substantial economic burden on the healthcare system. 4,5 The head is the most common site for NMSC, and certain areas on the face (ears, nose, periorificial, chin and mandible areas) are high-risk areas for recurrence and metastasis of skin cancer. 3,4 Many of the earlier large-series studies on the incidence of NMSC report only crude anatomical sites such as face or head and neck and do not specify incidence of NMSC on specific subsites of the face such as the ear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 161 primary articles were identified and analyzed for the development of the supporting evidence tables for the MMS AUC: 53 for basal cell carcinoma (BCC), 63 for squamous cell carcinoma (SCC), 23 for LM and melanoma in situ, 20 for dermatofibrosarcoma protuberans, 10 for microcystic adnexal carcinoma, 9 for atypical fibroxanthoma and malignant fibrous histiocytoma, 8 for Merkel cell carcinoma (MCC), 8 for leiomyosarcoma,…”
Section: Methodsmentioning
confidence: 99%